Perpaduan Budaya Pada Bangunan Gereja Kristen Jawi Wetan Wiyung Surabaya - Elita Amanda Limawandoyo (Intra, 2013)
Acceptance of Christianity in Indonesia, especially in East Java in the 1800s made GKJW (Jawi Wetan Christian Church) has a different liturgy and buildings with other Christian churches in Indonesia. In this study will be discussed how the influence and embodiment blend of Javanese culture with Christian culture that looks physically in the GKJW Wiyung Building, with uses descriptive qualitative method. And the results of the research will demonstrate the fusion of cultures are in this church.